The dynamics of migration and economic growth: A comparative perspective on the USA, Australia, and Germany (International Journal of Management and Sustainability, 2025)
This study presents a thorough examination of the economic effects of net migration in the United States, Australia, and Germany from 1960 to 2022, using the Autoregressive Distributed Lag (ARDL) model to assess short- and long-term effects. The findings reveal divergent results. In the United States, migration has no statistically significant effect on economic growth in either period, suggesting that migration cannot sustain growth without complementary measures. In contrast, Australia has a substantial positive correlation between net migration and real GDP per capita, highlighting its role in long-term economic stability. However, in Germany, the effect is only significant in the short term. These findings imply that the effects of migration on the economy are not always consistent and can be impacted by several variables, including fiscal policy and the demands of the labor market today. Therefore, the current study emphasizes the importance of creating migration policies that are flexible enough to respond to both short-term economic fluctuations and long-term structural economic changes.